Therapeutic effectiveness of treatment measures for nematodoses of the digestive tract of cattle - Yevstafieva, V.; Budnyk, D.; Melnychuk, V.; Kyrychko, B.; Derkach, I. (Scientific Progress & Innovations, 2024)
Invasive diseases are widespread throughout the world and cause significant economic losses to livestock. Among the most common infestations in cattle, nematodoses of the digestive tract occupy one of the leading places in terms of relevance. These diseases are mostly chronic and are accompanied by damage to the intestinal mucosa and rennet, changes in the composition and activity of the microflora, and a decrease in immunity and productivity of animals. The use of anthelmintic drugs in the fight against parasitoses ensures the liberation of the animal body from helminths and at the same time does not affect the restoration of the normal composition of the intestinal microflora. The aim of the research was to establish the effectiveness of treatment measures for trichurosis and strongyloidoses of the digestive organs of cattle. Under experimental conditions, the anthelmintics Fenzol 22 % (AS – fenbendazole) and Novoverm 1 % (AS – aversectin C) were tested in combination with the symbiotic Enteronormin (probiotics – lactic acid bacteria Enterococcus faecalis, Lactobacillus salivarius and spore-forming bacteria Bacillus subtilis; prebiotics – water-soluble chitosan, peptones). The conducted studies established that Fenzol 22 % anthelmintic was more effective than Novoverm 1 % both for strongyloidoses of the digestive organs and for trichurosis. On the 30th day of the experiment, the extensive and intensive effectiveness of Fenzol 22 % was respectively 100 % for nematodes, Novoverm 1 % – 66.7 and 86.3 % for trichurosis, 100 % – for strongyloidoses of the digestive tract. At the same time, the application of anthelmintics to infested animals in combination with the symbiotic Enteronormin increases the effectiveness of treatment measures for nematodoses of the digestive tract and reaches 100 % in 30th days. The recovery period for cattle when using Fenzol 22 % for trichurosis is 30 days, when using Fenzol 22 % and Novoverm 1 % for strongyloidoses of the digestive organs – 10 and 30 days. The recovery period of animals when using complex treatment is reduced to 10 days for trichurosis, for strongyloidoses of the digestive organs – to 5 days. The results of the conducted research proved the expediency of using probiotics and prebiotics in complex therapy of cattle for trichurosis and strongyloidoses of the digestive organs.